Contextos e práticas funerárias no Baixo Tapajós : um estudo dos sepultamentos em urna no sítio Paraná de Arau-é-pá - Costa, Ádrea Gizelle Morais (2015)
In the Amazon the burial practices carried out by prehistoric peoples are explored and studies of bone and traces of the contexts involved even less discussed. The study of funerary contexts are made later excavations of the site, and this hinders understanding of the contexts involved in addition to making more difficult the analysis and interpretation of the collected material associated with the burials. In this context, this study aims to identify places with funerary contexts in the lower tapajós, specifically the area comprising the city of Aveiro in the State of Pará, focusing the burials in urns tradition related item-dotted encountered during the archaeological survey of the site Paraná de Arau-is-man in 2009 carried out under the technical supervision of archaeologist Dr. Denise Pahl Schaan. And from the study of these burials using methods proposed by Arqueotanatologia and Bioarqueologia this paper sought to identify and understand the funerary contexts present in the place of Paraná de Arau-é-pá.